Suicide rates in Germany in lockdown and non-lockdown phases during the COVID-19 pandemic in 2020/2021 - Anne Elsner; Roland Mergl; Antje-Kathrin Allgaier; Ulrich Hegerl (PLoS ONE, 2025)
Contrary to the cautions of many, suicide rates during the first COVID-19 pandemic lockdown in Germany did not rise, but declined. With the accessibility of the 2021 weekly suicide data, it was possible to analyze suicide rates and the proportion of suicide methods during the lockdown and non-lockdown phases and during the first 21 months of the pandemic compared to the previous ten years. An interrupted time-series analysis based on a linear regression was used. For the comparisons of predicted and observed suicide rates, excess suicide mortality rates (ESMR) were chosen among others. Changes in the choice of method were analyzed by comparing the rates of different methods in lockdown- and non-lockdown phases. Since the start of the COVID-19 pandemic, suicide mortality in 2020/2021 was significantly higher than expected (ESMR = 1.0161; 95% CI: 1.0005; 1.0317). Registered suicide mortality was lower than expected during the lockdown phases in these years (ESMR = 0.9477; 95% CI: 0.9128; 0.9825) and higher during non-lockdown phases (ESMR = 1.0353; 95% CI: 1.0178; 1.0528). A MANOVA revealed a significant difference of the absolute number of suicides between lockdown and non-lockdown periods (factor “lockdown”: F(1,100) = 9.47; p = 0.003). A shift of suicide methods in the comparison of these periods could not be detected. Our results are in line with the rise in yearly absolute numbers of suicides in 2022 in Germany and illustrate that even though suicide rates declined during lockdowns, there was a general rise since the beginning of the COVID-19 pandemic, especially during the non-lockdown periods. This hints towards a “postponement effect”, probably as loosening of the lockdown restrictions makes suicide methods more easily accessible and more suicides than expected are present in the following non-lockdown periods. More research is needed to better understand the mechanisms influencing suicidality during lockdowns and the COVID-19 pandemic in general.